The Role of Ankle and Knee Joints Proprioceptive Acuity in Improving the Elderly Balance After 8-Week Aquatic Exercise - Ramin Beyranvand; Mansour Sahebozamani; Abdolhamid Daneshjoo (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Proprioception improvement in lower limb joints plays an important role in reducing falling risk in the elderly. Since proprioception improvement in the lower limb joints have the most relevance to better balance in the elderly, this study aimed to investigate the role of ankle and knee joint proprioception on balance improvement in the elderly after an aquatic exercise program. Methods & Materials total of 30 elderly male (60-70 years old) were randomly selected and classified into intervention and control groups. Postural sway parameters and proprioception acuity were evaluated using the Biodex balance system and photography method, respectively. Then the intervention group participated in an aquatic exercise program for 8 weeks while the control group did not receive any intervention. All subjects were reassessed upon completion of the intervention program and the Pearson correlation test was used for data analysis (P≤0.05). Results The results of this study showed a significant relationship between the changes of the ankle joint proprioception and the postural control ability after conducting the 8 weeks of aquatic exercise program (P<0.05); while the above relationship was not significant in the case of the knee joint (P>0.05). Conclusion It seems that the improvement in ankle joint proprioception plays a more important role in improving the postural control ability of the elderly compared with the other lower limb joints. Accordingly, it is recommended that the special role of the ankle joint should be more considered in the exercise planning for balance improvement in the elderly.